Territorial Resistance and Peasant Food Systems in Brazil - Origuéla, Camila Ferracini [UNESP] (Springer Nature, 2022)
This chapter is aimed at analysing territorial resistance and peasant food systems built by socio-territorial movements, such as the Landless Rural Workers Movement (Movimento dos Trabalhadores Rurais Sem-Terra—MST). Territorial resistance can be understood as struggles, actions, practices, organisations, and autonomous and emancipatory techniques and technologies created and applied by peasant movements in a given space for food production, processing, and commercialisation, especially agroecological food.